Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø±Ø³ÙˆÙ„ ÙÙŠ ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø£Ø·ÙØ§Ù„ (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© ÙÙŠ ØØ¯ÙŠØ« Ø³Ù†Ù† Ø§Ù„ØªØ±Ù…ÙŠØ°ÙŠ Ø§Ù„Ø±Ù‚Ù… 2516) - Ahmad Natsir (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2018)
In Islamic education, hadith became the second foundation after the Qur'an. By relying on education to the two great principles, an ideal education is expected to be realized as a place to create a generation of faithful and knowledgeable knowledge. In sunan al-Tirmidhi, there is a hadith numbered index of 2516 beginning with ihfaz} Alla> h yah} faz} ka, the hadith by Ibn Hajar al-Asqala> ni> is placed in chapter al-zuhd wa al-wara, and by al- Nawa> wi> in Riyad} al-S} a> cf} i> n is placed in the chapter of Al-Mura> qabah, whereas the hadith by the Messenger of Allah. submitted to Abdullah Ibn Abbas at the age he has not reached baligh even there has not been 10 years. Departing from anxiety in the form of severe Hadith subdance but delivered to a friend who is not yet 10 years old this researcher tried. (1) revealing the quality of the traditions in Sunan al-Tirmidhi> index number 2516. (2) disclosing how the Prophet's method of educating the child. In the end the writer concludes the hadith Sunan al-Tirmidhi> 2516 index number belongs to the hasan sahih hadith and the method of Prophet in educating the child contained in the hadith is the method mauiz ah but when the mauizah contains substantial enough weight then it is delivered with the selection of words, time and circumstances are absolutely right.